Pemaksaan Perkawinan oleh Orang Tua terhadap Anak di Bawah Umur: Tinjauan Hukum Perlindungan Anak dan Hak Asasi Manusia - Afgan Fairuz (Jurnal Hukum Lex Generalis, 2025)
Cases of forced marriage by parents against minors remain a serious issue in Indonesia, despite laws that have established a minimum legal age for marriage and guaranteed the protection of children’s rights. This practice generally begins with a unilateral decision by parents to arrange a marriage for their child, who is still a student, with a certain partner due to economic reasons, social pressure, customary expectations, or concerns about family honor. In many cases, the child is not given the opportunity to provide free and full consent and instead experiences psychological pressure and the loss of opportunities to continue education and determine their own future. This situation creates a conflict between ongoing social practices and national legal provisions that prioritize the best interests of the child. This study aims to examine the legal framework for protecting children from forced marriage and to analyze it from a human rights perspective. The research uses a normative legal method with statutory and conceptual approaches. The results indicate that forced marriage against minors constitutes a violation of children’s rights and can be categorized as psychological violence, as well as contradicting the principle of free consent in marriage. Furthermore, the practice of marriage dispensation still has the potential to legitimize child marriage. Therefore, stronger legal protection, improved supervision, and active involvement of the state and society are necessary to ensure the protection of children’s rights as legal subjects.